Arctic Europe: Bringing together the EU Arctic Policy and Nordic cooperation - Stępień, Adam; Koivurova, Timo (Valtioneuvoston kanslia, 2017)
The study considers how the European Union’s Integrated Policy for the Arctic can productively interact with Nordic cooperation frameworks in order to support developments in Arctic Europe. Common themes of Nordic cooperation and the EU’s Arctic policy include: Arctic bioeconomy, innovative cold climate technologies, digitization, and facilitating circular economy solutions suitable for sparsely populated areas. EU-Nordic cooperation as regards tackling border obstacles should continue, with special attention to enhancing trans-border activities of the Sámi. The EU-Arctic Stakeholder Forum process should be used as a catalyst in the formulation of common strategy for Arctic Europe, potentially based on the logic of smart specialization. In order to support drafting of project proposals that address common priorities, a special seed money facility could be established. Common EU-Nordic Arctic conferences could enhance long-term cooperation between various programmes. Arctic Europe is an integral and indispensable part of the socio-economic landscape of the EU. In-vestments in the region can benefit whole Europe. Region has potential to facilitate innovative solutions fueling European green growth. It can be the first stage for European companies’ expansion to other parts of the circumpolar Arctic. Europe’s northernmost regions can increasingly act as living labs for new technologies and new governance solutions. Arctic Europe remains an important part of Europe’s cultural and natural landscape and a source of natural resources for the European economy. The success of Arctic Europe will enhance its role as the EU’s gateway to Russia and the Arctic.